Peningkatan Kapasitas Kader Kesehatan Remaja Melalui Program Asmara - Ayo Selamatkan Masa Remaja Untuk Pencegahan Perilaku Berisiko di SMPN 23 Padang - Abdiana; Firdawati; Hardisman; Husna Yetti; Ida Rahmah Burhan; Rosfita Rasyid; Yuniar Lestari; Rima Semiarty; Adila Kasni Astiena; Zurayya Fadila; Nelmi Silvia; Rizanda Machmud (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Adolescence is a transitional period that is vulnerable to the emergence of risky behaviors, such as smoking, promiscuity, and lack of health concern. These behaviors can negatively impact adolescent growth and development physically, mentally, and socially. This community service activity aims to increase knowledge and awareness regarding preventing risky behaviors through a health education program for students of SMPN 23, Padang City. The activity methods include preparation and problem identification stages, coordination with partners, and implementation stages, including interactive counseling, group discussions, and distribution of leaflets and promotional banners. The first day of education targeted all students in grades VII and VIII of SMPN 23 Padang. On the second day, education focused on members of the Adolescent Health Cadre (KKR) and the Student Council (OSIS), totaling 27 people. Evaluation was carried out with pre-tests and post-tests to measure the increase in knowledge. The activity results showed a significant increase in the average knowledge score of the cadre students (77.78 to 94.07). In addition, the students showed enthusiasm and active involvement throughout the activity. This educational activity was successfully implemented smoothly and brought about an increase in knowledge among students, KKR cadres, and OSIS. Cadre students understand their role and are expected to be able to serve as peer educators when their peers encounter health issues or risky behavior. Similar activities, involving teachers and parents, need to be implemented continuously to optimize risky behavior prevention.